(untitled) (Research, Society and Development, 2025)
Polycystic Ovary Syndrome (PCOS) is an endocrine-metabolic disorder characterized by elevated testosterone levels, ovulatory dysfunction, polycystic-appearing ovaries, irregular gonadotropin secretion, low-grade inflammation, hyperandrogenism, and hirsutism that lead to infertility, spontaneous abortions, and pregnancy complications. Additionally, patients with PCOS have an increased risk of peripheral insulin resistance, obesity, hyperlipidemia, hypertension, cardiovascular disease, and cancer. Considering the complexity of the disease, this narrative literature review aimed to investigate the role of intestinal modulation as a possible alternative therapeutic approach in the treatment of PCOS. To this end, 27 scientific articles published in Portuguese and English between 2006 and 2024 were selected and available in the main databases: National Library of Medicine (PubMed), Web of Science, Scientific Electronic Library Online (SciELO), Google Scholar, Medical Literature Analysis and Retrieval System Online (MEDLINE) and Virtual Health Library (VHL). Intestinal modulation through probiotics and prebiotics was able to promote; when associated with lifestyle changes, improvements in the reduction of free androgens, inflammatory markers, transaminases, lipid parameters and insulin resistance; increased SHBG and nitric oxide. Furthermore, there was an improvement in the waist-to-hip ratio and weight of patients, favoring the reduction of inflammatory stress and the influence of the obesogenic condition.